2018
DOI: 10.4236/ijcm.2018.911066
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Awareness towards Chronic Kidney Disease Risk Factors in Saudi Arabia

Abstract: Background: The risk of CKD is high in Saudi Arabia due to increasingly growing prevalence of its risk factors, such as diabetes, hypertension and obesity. Therefore, the objective of this study was to assess the level of awareness of Saudi population towards CKD risk factors in order to generate platform for future planning. Methodology: This study included 940 apparently healthy Saudi volunteers, their ages ranging from 17 to 65 years old with a mean age of 35 years. A purposeful questionnaire was designed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
1
6
0
2
Order By: Relevance
“…Education came out as a significant factor of awareness, where patients with bachelor's degrees exhibited better awareness levels than patients who are less educated. This is consistent with the report of Sa'adeh et al [ 19 ], as well as Ahmed et al [ 21 ], who reported that greater knowledge levels were significantly predicted among patients with higher educational levels. However, this has been contradicted by the report of Plantinga et al [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Education came out as a significant factor of awareness, where patients with bachelor's degrees exhibited better awareness levels than patients who are less educated. This is consistent with the report of Sa'adeh et al [ 19 ], as well as Ahmed et al [ 21 ], who reported that greater knowledge levels were significantly predicted among patients with higher educational levels. However, this has been contradicted by the report of Plantinga et al [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“… 14 Another study among the Saudi population by Ahmed et al reported that out of 940 participants, about 60% correctly identified DM and HTN as risk factors of CKD. 11 However, a recent study among the Australian public reported that 60.6% of the participants identified DM as a risk factor for CKD, but only 38.3% identified HTN as a risk factor for CKD. 12 Similar to our study, lower identification of DM and HTN as risk factors of CKD was also reported from Hong Kong, Nigeria, Singapore and Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Higher rate of early identification of individuals with undetected/early CKD or those at risk of developing CKD might be possible among populations with high levels of knowledge and awareness about CKD. 11 Studies conducted in both developed and developing countries have shown that the public understanding of CKD and its risk factors are relatively poor. 12 A recent Australian study found limited knowledge among participants regarding the physiological role of the kidneys, and less than half of the participants correctly identified hypertension as a risk factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A better rate of early identification of those with undetected/early CKD or those at risk of developing CKD may be attainable in populations with high levels of knowledge and awareness about CKD [ 15 ]. According to research conducted in both developed and developing nations, the public’s understanding of CKD and its risk factors is inadequate [ 16 ].…”
Section: Introductionmentioning
confidence: 99%